Aktivitas antibakteri flavonoid propolis Trigona sp terhadap bakteri Streptococcus mutans (in vitro) (In vitro antibacterial activity of flavonoids Trigona sp propolis against Streptococcus mutans) - Ardo Sabir (Dental Journal (Majalah Kedokteran Gigi), 2005)
A number of investigations have shown a positive correlation between the number of Streptococcus mutans (S. mutans) in dental plaque and the prevalence of dental caries. Consequently, this microorganism has been the prime target for the prevention of dental caries. Propolis being a substance made by the honeybee, is a potent antibacterial agent. The main chemical class present in propolis is flavonoids. Flavonoids are well-known plant compounds that have antibacterial property. Because S. mutans is accepted to be one of the microorganisms responsible for dental caries and flavonoids in propolis are antibacterial, the purpose of this study was to evaluate in vitro the antibacterial activity of flavonoids Trigona sp propolis against S. mutans as a first step in its possible use as an alternative anticaries agent. Extract flavonoids was purified from ethanol extract of propolis which was obtained from Bulukumba Regency South Sulawesi using thin layer chromatography. The purification of flavonoids was carried-out by UVradiation at λ max 254 nm and λmax 366 nm and treatment with ammonia. Extract flavonoids was diluted in aquadest to 0.05%; 0.075%; 0.1%; 0.25%; 0.5%; 0.75% concentrations. Aquadest and 10% Povidone iodine were also used as control solution. S mutans were grown in medium glucose nutrient agar and incubated with flavonoids for 24 and 48 hours, at 37° C. Antibacterial activity was reflected by the diameter of the inhibition zones around the stainless steel cylinder. The data were analyzed by using ANOVA followed by LSD test with significance level of 5%. The results of this study showed that after being incubated for 24 and 48 hours, all flavonoid concentrations significantly (p < 0.05) inhibited the growth of S mutans. 0.1% flavonoid was the most effective concentration to inhibit the growth of S mutans after 24 hours of incubation and 0.5% flavonoid after 48 hours of incubator.